Renal medullary changes in renal allograft recipients with raised serum creatinine. Issue 4 (3rd February 2006) - Sis, B; Sarioglu, S; Celik, A; Kasap, B; Yildiz, S; Kavukcu, S; Gulay, H; Camsari, T
Abstract : Objective: To test the hypothesis that the renal medulla may reflect rejection related changes and thus have a predictive value in the assessment of acute renal allograft rejection or chronic graft damage. Methods: 75 post-transplant biopsies from 57 patients were scored according to the Banff 1997 scheme. The biopsies with adequate cortical and medullary tissue (n = 23) were selected and medullary tissues were reviewed for rejection related lesions except intimal arteritis. Chronic damage was determined by image analysis depending on periodic acid-methenamine silver (PAMS)-Masson trichrome (MT) staining. Medullary and cortical changes were compared. Results: Interstitial inflammation and tubulitis were more frequent and severe in the cortex (p<0.001). Medullary tubulitis was associated with intimal arteritis (p = 0.003, r  = 0.598). Medullary interstitial inflammation (n = 8) and tubulitis (n = 4) were associated with cortical borderline changes (n = 5) or allograft rejection (n = 3). The sensitivity, specificity, and positive and negative predictive values of medullary inflammatory changes in predicting cortical allograft rejection were 43%, 69%, 37%, and 73%, respectively. A significant association was observed between medullary MT-SAP and cortical PAMS-SAP values (p = 0.02, R 2  = 0.23). Conclusions: Acute rejection related lesions are more common and severe in the cortex, and the renal medulla does not sufficiently reflect cortical rejection. The positive and negative predictive values of medullary changes for allograft rejection are low, and medullary inflammation is not a reliable indicator of allograft rejection. Increased medullary fibrosis is correlated with chronic cortical damage.